Gratitude as a predictor of fear of missing out (FOMO) among digital native generation in Yogyakarta - Rosyida, Amalia; Romadhani, Rahmatika Kurnia (Faculty of Psychology, Universitas Negeri Yogyakarta, 2022)
The Fear of Missing Out (FoMO) is widely experienced by individuals in the digital era. Various studies have shown that FoMO adversely affects on the physical and psychological conditions of individuals who experience it. On the other hand, some experts argue that gratitude can be a protective factor from the emergence of FoMO. This study aims to determine the role of gratitude on FoMO among digital native generation. This study used a quantitative approach, conducted in the Special Region of Yogyakarta (DIY) with an online survey through psytoolkit. This study was participated by 599 respondents with nonprobability accidental sampling method. The data collection tool used was the Fear of Missing Out (FoMO) scale and the Indonesian version of the gratitude scale. The data analysis technique used was simple linear regression analysis with the help of SPSS 24. The hypothesis of this study is accepted, that it is stated that there is an effect of gratitude on FoMO in digital native generation with a coefficient of determination by 0.077, which means that the effect of gratitude on FoMO is 7,7% with the regression line equation of Y= 49,248 + (-0,090)X.